"If Dragons 'Would Eat' [sic] Pink Hearts, That Would be OK": Preadolescent Boys' Paths to Reading - Geneviève Brisson (Canadian Society for Studies in Education, 2012)
This article explores a study of five preadolescent boys' perceptions of reading and readers, and the role of agency on their reading paths. The boys, in grades five to seven, shared their thoughts and experiences through individual and group interviews. The findings suggest that these boys adapted norms and practices of the dominant discourse among their male friends to pursue their own interests in reading. Some participants, however, stated they sometimes experience pressure to assume gender-appropriate preferences in order to be accepted by their (male) peers.